Chapter 11: Debates and Dichotomies: Exploring the Presumptions Underlying Contentions About the Geography of Armed Conflict. (2nd February 2015) - Blank, Laurie R.
Abstract: An examination of the growing literature on the topic of the geography of armed conflict suggests that the differences of opinion, between and among academics, policymakers and military lawyers, for example, are nearly intractable. Statements about the propriety of a certain target under the law of armed conflict are often met by pronouncements regarding the role of jus ad bellum in cabining the use of force in the territory of another state or the restrictive parameters of the international human rights/law enforcement regime for addressing individuals who pose a threat or danger to others. Indeed, one might easily conclude that the participants in these debates are simply operating in entirely separate analytical paradigms, leading to interesting and challenging intellectual discussions but not to productive conversations that advance the analysis and move beyond the debate to effective potential resolution of a complicated and multi-layered issue. However, unlike pornography or terrorism, where notwithstanding a myriad of different definitions, "you know it when you see it", little agreement exists even on whether there is a specific, definable geography of armed conflict at all. To help move beyond this impasse, this article explores the presumptions underlying the ongoing debates regarding the geography of armed conflict, in an effort to untangle the debates and provide new opportunities and venues for discussion—and thus to help advance the development of the law of armed conflict and other relevant bodies of law. These presumptions appear in particular in four dichotomies that inherently help drive the debates but are brushed aside or not taken into consideration: law versus policy; authority versus obligation; territory versus threat; and submission of the collective enemy versus elimination of an individual threat. For each or any of these dichotomies, the lens through which one views the contrasting positions will then have a significant—if not determinative—effect on considerations and conclusions regarding questions of geography and the battlefield. As a result, recognizing these dichotomies and understanding how they impact the current discourse is critical to any effective conversation, whether in the academic or policy arenas.